835 The Use of In-patient Concussion Consultation for Patient Education as a Model for Anticipatory Guidance in a Cohort of Pediatric Patients to Improve Symptom Score and Associated Health Outcomes. (1st March 2022) - Henson, Jeffrey Curran; Hanks-Clark, Elizabetheth; Cook, Alicia; Ocal, Eylem
Abstract : INTRODUCTION: It is estimated that 10% of all pediatric emergency room visits are due to concussions, and although most children recover without complications, problems including physical, emotional, somatic symptoms and sleep disturbances may occur. Pediatric populations are especially sensitive to these damaging sequelae as the plasticity of the developing neural networks of children are highly dynamic. It is with these considerations we have decided to undertake this study to evaluate if early in-patient concussion consultation in patients who have suffered traumatic brain injury (TBI) decreases recovery time, increases symptom reduction, and improves recovery to baseline neurocognitive functioning. METHODS: The patient cohort consisted of an initial 74 patients who were an in-patient concussion consultation using the acute concussion evaluation (ACE) tool to assess symptom score [0-22]. Patient files were queried for demographic information, comorbidities, and covariates of interest. The primary endpoints are clinical follow-up and reduction in symptom score between initial evaluation and clinical follow-up. All statistical analysis was performed using a significance level of α = 0.05. RESULTS: Delta score as a primary outcome was assessed only on patients retained during clinical follow-up. The difference in initial consult score compared to score at clinical follow-up was significant, p < 0.001, with means of 12.125, and 3.889 respectively. Delta score was found to have resulted in a mean 8.289 reduction in symptom score, and a positive correlation was observed between initial symptom score and delta score. The results for linear and logistic regression of covariates will be presented during CNS 2021. CONCLUSIONS: The use of an in-patient concussion consultation provides families with an invaluable tool regarding education and management of concussion symptoms. Our initial results verify this modality of early intervention as an important tool to educate and highlight the importance of early engagement in increasing clinical retention and reducing concussive symptoms in this sensitive patient population.